Effects of sex, host-plant deprivation and presence of conspecific immatures on the cannibalistic behavior of wild Ascia monuste orseis (Godart) (Lepidoptera, Pieridae) - Santana,Alessandra F. K. (2011)
Effects of sex, host-plant deprivation and presence of conspecific immatures on the cannibalistic behavior of wild Ascia monuste orseis (Godart) (Lepidoptera, Pieridae). The specialist cabbage caterpillar Ascia monuste orseis (Lepidoptera, Pieridae) feeds on plants of the Brassicaceae family, but may eventually ingest conspecific eggs and larvae during the larval stage. The present study examines feeding behavior of 4th and 5th instar cabbage caterpillars in relation to sex, host-plant deprivation and presence of conspecifics. We recorded number of egg ingested per larvae, developmental indices and duration of feeding, exploratory and resting behavior. Kale deprived caterpillars presented high rates of cannibalism, development delay and decreased fecundity. Cannibalism rates were not influenced by the sex of the larvae. In general, the presence of conspecific eggs did not interfere with the frequency and duration of the categorical behavioral events. We conclude that food availability is a strong factor influencing the extent to which A. monuste orseis caterpillars cannibalize.